2017
DOI: 10.1007/s12178-017-9399-2
|View full text |Cite
|
Sign up to set email alerts
|

Bias in cervical total disc replacement trials

Abstract: Purpose of review Cervical disc replacement (CDR) has emerged as a motion-preserving alternative to anterior cervical discectomy and fusion in selected cases. Despite favorable literature, CDR is not universally accepted because of concerns regarding bias in the existing literature. The purpose of this review is to identify the possible biases in the disc replacement literature. Recent findings Recent studies that compare CDR and ACDF have demonstrated equivalent or superior outcomes, lower rates of secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Mounting evidence supports cervical TDR (although not without conflict). 24 25 26 27 28 29 Lumbar TDR, on the other hand, is treated more cautiously: comparisons with standard fusion techniques by independent, non-industry-backed studies are few, pooled data are conflicting, 30 and long-term follow-up is scarce. 31…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence supports cervical TDR (although not without conflict). 24 25 26 27 28 29 Lumbar TDR, on the other hand, is treated more cautiously: comparisons with standard fusion techniques by independent, non-industry-backed studies are few, pooled data are conflicting, 30 and long-term follow-up is scarce. 31…”
Section: Discussionmentioning
confidence: 99%
“…In a previously published RCT on cervical radiculopathy due to degenerative disk disease, 83 patients were operated with ADR (DiscoverTM, DePuy Spine, Johnson and Johnson, Raynham, Massachusetts, U.S.A.) at one or two levels [11,12]. The patients who had undergone revision surgery or Portions of this work were presented in podium presentation form at the CSRS 44th Annual Meeting, Toronto, Canada, December 1-3, 2016, at the CSRS 33th Annual Meeting, Salzburg, Austria, May [24][25][26]2017, and at the CSRS 47th Annual Meeting, New York, USA, November [21][22][23]2019.…”
Section: Methodsmentioning
confidence: 99%
“…The sponsors were not involved in the study design, conduct of the trial, data analysis, interpretation of the results or the writing of the manuscript. There is therefore a lesser risk for publication, external validity, confirmation or financial conflict of interest bias, the four sources of bias defined by Radcliff et al [24].…”
Section: Prevalence Of Homentioning
confidence: 99%
“…[3] Several types of bias can be associated with industry-funded trials. Radcliff et al [46] identified four types of bias present in cervical arthroplasty trials: publication bias (tendency to publish studies with positive results), external validity (the extent to which the study results can be applied to situations outside of study conditions), confounding bias (a distortion that modifies an association between an exposure and an outcome because a factor is independently associated with the both), and financial conflicts of interest. Similar types of bias can be applied to other subspecialties of neurosurgical research funded by the industry.…”
Section: Trial Implementation Fundingmentioning
confidence: 99%